Penerapan Modul Elektronik Sigil pada Materi Fluida Statis untuk Meningkatkan Kompetensi Pengetahuan dan Kedisiplinan Peserta Didik - Febri Cahyo Pujiyanto; Rini Budiharti; Elvin Yusliana Ekawati (Universitas Sebelas Maret, 2023)
This action research has the aim of (1) Improving students' knowledge ability through the application of scientific-based sigil electronic modules on Static Fluid material, (2) Increasing student discipline through the application of scientific-based sigil electronic modules on Static Fluid material. The research design is classroom action research (PTK) model Kemmis and Mc. Taggart model through two cycles. Data collection techniques used include observation techniques, tests, checklists, interviews and document reviews. Then the data analysis technique consists of qualitative and quantitative analysis. To test the validity of the data using triangulation techniques. The results showed that the application of Sigil electronic modules based on scientific material on Static Fluid was able to improve the knowledge and discipline skills of XI MIPA 3 SMA Negeri 1 Kartasura students. The percentage of knowledge ability completeness increased from 41.67% during the pre-cycle stage, to 61.11% in cycle I, and reached 91.67% in cycle II. The percentage of students' discipline achievement also increased. In the pre-cycle of 36 students, there were no students with good and very good discipline categories, increasing to 26 students with good and very good discipline and to 33 students in cycle II.